What accounts for the association between late preterm births and risk of asthma? - Voge, Gretchen A. (Allergy Asthma Proc, 2017)
BACKGROUND: Although results of many studies have indicated an increased risk of asthma in former late preterm (LPT) infants, most of these studies did not fully address covariate imbalance. OBJECTIVE: To compare the cumulative frequency of asthma in a population-based cohort of former LPT infants to that of matched term infants in their early childhood, when accounting for covariate imbalance. METHODS: From a population-based birth cohort of children born 2002–2006 in Olmsted County, Minnesota, we assessed a random sample of LPT (34 to 36 6/7 weeks) and frequency-matched term (37 to 40 6/7 weeks) infants. The subjects were followed-up through 2010 or censored based on the last date of contact, with the asthma status based on predetermined criteria. The Kaplan-Meier method was used to estimate the cumulative incidence of asthma during the study period. Cox models were used to estimate the hazard ratio and 95% confidence interval for the risk of asthma, when adjusting for potential confounders. RESULTS: LPT infants (n = 282) had a higher cumulative frequency of asthma than did term infants (n = 297), 29.9 versus 19.5%, respectively; p = 0.01. After adjusting for covariates associated with the risk of asthma, an LPT birth was not associated with a risk of asthma, whereas maternal smoking during pregnancy was associated with a risk of asthma. CONCLUSION: LPT birth was not independently associated with a risk of asthma and other atopic conditions. Clinicians should make an effort to reduce exposure to smoking during pregnancy as a modifiable risk factor for asthma.